Nonlinear modeling, characterization, and effectiveness of three-degree-of-freedom piezoaeroelastic energy harvesters - Bouma, A.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (Elsevier, 2023)
Modeling and performance investigation is conducted on a three-degree-of-freedom piezoaeroelastic system with freeplay and multi-segmented stiffness with and without impact. A piezoelectric transduction mechanism is considered in the plunge degree of freedom and the aerodynamic loading is modeled with the unsteady representation based on the Duhamel formulation, including the stall phenomenon. The typical aeroelastic section model is comprised of a pitching and plunging airfoil with a control surface containing freeplay and multi-segmented stiffness springs in the pitch and control surface motions. Nonlinear characterization is conducted on the response of the energy harvesting system when changing the nonlinear stall coefficient, freeplay gap size in the pitch and control surface springs, and the multi-segmented nonlinear stiffness to simulate impact. Results show that grazing and grazing/sliding bifurcations may be present, and the response is complex with several transitions as the wind speed is increased. Additionally, the presence of freeplay and multi-segmented nonlinearities allow for energy harvesting at speeds smaller than that of the linear flutter velocity. An effective design is determined for a three-degree-of-freedom wing-based energy harvester by selecting the freeplay gap size and multi-segmented nonlinear stiffness in the pitch and control surface and the electrical load resistance.
Keywords: Aeroelasticity; Characterization; Energy harvesting; Nonlinear dynamics; Three-degree of freedom